Some applications of IFS based on square symmetries - Bareikis, Gintautas; Maciulis, Algirdas (Nonlinear Analysis: Modelling and Control, 2012)
This paper describes a fractal based method for generating the pseudorandom permutations. We construct an Iterated Function System (IFS) belonging to the class of square symmetries and simulate the pseudorandom walk on a square. In this way some families of key based permutations are generated. The cardinalities of generated families are analysed.
Keywords: key based permutation; iterated function system; square symmetries